2017
DOI: 10.1111/iej.12783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic activation on the reduction of bacteria and endotoxins in root canals: a randomized clinical trial

Abstract: Nakamura VC, Pinheiro ET, Prado LC, Silveira AC, Carvalho APL, Mayer MPA, Gavini G. Effect of ultrasonic activation on the reduction of bacteria and endotoxins in root canals: a randomized clinical trial. Journal, 51, e12-e22, 2018. Aim This randomized clinical trial aimed to compare the effectiveness of ultrasonic activation with that of nonactivated irrigation on the removal of bacteria and endotoxin from root canals. Methodology Fifty patients with necrotic pulps and asymptomatic apical periodontitis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0
51

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 44 publications
11
40
0
51
Order By: Relevance
“…Moreover, it seems that greater the volume of irrigation used, greater was the LPS reduction (Nakamura et al . ). All the four studies included in this review reported a similar sequence and volume of the chemical auxiliary substances used during chemomechanical preparation (Gomes et al .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it seems that greater the volume of irrigation used, greater was the LPS reduction (Nakamura et al . ). All the four studies included in this review reported a similar sequence and volume of the chemical auxiliary substances used during chemomechanical preparation (Gomes et al .…”
Section: Discussionmentioning
confidence: 97%
“…Esse estudo foi realizado de acordo com as normas CONSORT (Consolidated Standards of Reporting Trials) para estudos clínicos randomizados. A metodologia utilizada para as coletas e análises microbiológicas foi baseada em estudos clínicos prévios (Pinheiro et al, 2015;Nakamura et al, 2018).…”
Section: Methodsunclassified
“…Os procedimentos clínicos foram realizados na Clínica de Pós-Graduação da (Nakamura et al, 2018). Os critérios de inclusão foram: pacientes com diagnóstico de necrose pulpar (confirmado pela resposta negativa ao teste de sensibilidade ao frio com gás refrigerante) e periodontite apical assintomática.…”
Section: Aspectos éTicosunclassified
See 2 more Smart Citations